2020
DOI: 10.3846/btp.2020.11354
|View full text |Cite
|
Sign up to set email alerts
|

Female Advantage? Management and Financial Performance in Microfinance

Abstract: The purpose of the article is to investigate whether female presence in microfinance institutions’ management team, i.e. board members, managers and loan officers, will improve their financial performance. We combine financial data on MFIs that is available from the MIX Market database with original data on the gender composition of MFIs’ management team, who include board members, managers and loan officers. This original dataset of 223 MFIs is analyzed using Logit-Tobit regression models with return on asset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 52 publications
1
21
0
2
Order By: Relevance
“…Although women are underrepresented on MFI boards (Mahadeo et al, 2012) research has found female board members are associated with better financial performance (Mersland and Strøm, 2009;Strøm et al, 2014;Chakravarty and Pylypiv, 2017;Vishwakarma, 2017) and social performance (Hartarska et al, 2014;Gohar and Batool, 2015;Velte, 2016;Gudjonsson et al, 2020). Hendry and Kiel (2004) also found that having women on the boards of MFIs helps to address gender inequality issues arising from institutional voids in part due to their own personal experiences.…”
Section: Diversitymentioning
confidence: 99%
“…Although women are underrepresented on MFI boards (Mahadeo et al, 2012) research has found female board members are associated with better financial performance (Mersland and Strøm, 2009;Strøm et al, 2014;Chakravarty and Pylypiv, 2017;Vishwakarma, 2017) and social performance (Hartarska et al, 2014;Gohar and Batool, 2015;Velte, 2016;Gudjonsson et al, 2020). Hendry and Kiel (2004) also found that having women on the boards of MFIs helps to address gender inequality issues arising from institutional voids in part due to their own personal experiences.…”
Section: Diversitymentioning
confidence: 99%
“…Several recent studies apply Tobit regression models (e.g. Gudjonsson et al , 2020). Examining the effect of female participation/empowerment on firm performance in Lebanese firm-level data, we estimate the following baseline model [2]:…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, our data are cross sectional covering the year 2013. From an econometric point of view, we use Tobit regressions, recently used by Gudjonsson et al (2020), to test the various hypotheses regarding the association between female participation/empowerment and firm performance.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the organizational ladder of MFIs, women can participate in three different important management positions – board members, managers, and loan officers (see Figure 1). Behavioral economics suggest the presence of a variation in economic decisions between male and female (Hartarska, Nadolnyak, & Mersland, 2014), and that the effects of women on various dimensions of MFIs performance (e.g., financial sustainability & social outreach) were significantly positive in general (Augustine et al, 2016; Boubacar, 2019; Ghosh & Guha, 2019; Gudjonsson, Kristinsson, Gylfason, & Minelgaite, 2020; Strøm, D'Espallier, & Mersland, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although, the role of women on the performance of MFIs is well established through rigorous and empirical research (Adusei, Akomea, & Poku, 2017; Bibi, Balli, Matthews, & Tripe, 2018; Boubacar, 2019; Ghosh & Guha, 2019; Gudjonsson et al, 2020; Memon, Akram, & Abbas, 2020; Pedrini, 2018; Vishwakarma, 2017), very little is known of the manifestation of women in the management role and clients base of the South Asian microfinance market. With the recent and remarkable progress in socio‐economic development of the South Asian countries, it is deemed important to examine how it has impacted gender diversity, particularly in the MFIs workforce.…”
Section: Introductionmentioning
confidence: 99%